Influence of Inter-row Gap Value on Turbine Losses - Paul G. A. Cizmas; Corbett R. Hoenninger; Shun Chen; Harry F. Martin (International Journal of Rotating Machinery)
This paper presents the results of a numerical investigation of the gap influence on the turbine efficiency. The rotor-stator interaction in a (1/2)-stage turbine is simulated by solving the quasi-three-dimensional unsteady Euler/Navier-Stokes equations using a parallelized numerical algorithm. The reduced turnaround time and cost/MFLOP of the parallel code was crucial to complete the numerous run cases presented in this paper. The inter-row gap effect is evaluated for 4 gaps, 3 radial positions and 3 angular velocities. As expected, the results presented in this paper show that the efficiency increases and losses decrease while the gap size increases. The maximum efficiency location, however, corresponds to values of the gap size which may be too large for practical use (approximately inch). Fortunately, a local maximum efficiency and minimum losses location has been found at approximately 0.5 inches gap size. The efficiency variation near the local optimum is large, in some configurations being as high as 1.4 points for a gap size variation of only 0.076 inches. Data produced by the numerical simulations can be used to develop a design rule based on the inter-row gap size.